Teacher's perception on the influence of the interior colors of selected preschool classrooms on the behavior of five-year old preschool children - See, Angelica Joy Marie T. (Animo Repository, 2006)
Studies on color and their effects have been interesting concept. Color therapy and color psychology are only some of the accepted and renowned topics concerning this notion. Specific colors have their own effects and taking the effort to understand them would be beneficial especially in the educational setting. The field of Early Childhood Education is slowly gearing towards understanding and applying this concept in preschool classrooms. Colors are now being taken into consideration when building an ideal classroom. Both administrators and education are taking part in making sure that their students are in a conducive learning environment. Teachers are seen as the authority in the area of teaching. They are privy to how the children behave in the classroom and what may be the reasons behind them. This then shows the importance of the teacher's thoughts and perspectives on how children are able to function and learn better. This paper discusses the teacher's perception on how interior colors influences children's behavior. It makes use of observation as well as interviews to provide the necessary data. With this thesis paper comes the initial step which would be favorable for both the educators and the students of the present and the next.